2010
DOI: 10.1016/j.jcta.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

On cross t-intersecting families of sets

Abstract: For all p, t with 0 < p < 0.11 and 1 t 1/(2p), there exists n 0 such that for all n, k with n > n 0 and k/n = p the following holds: if A and B are k-uniform families on n vertices, and |A ∩ B| t holds for all A ∈ A and B ∈ B, then |A ||B| n−t k−t 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 9 publications
(8 reference statements)
0
22
0
1
Order By: Relevance
“…In [20,21] a version of this result was proved for t-intersecting pairs of hypergraphs, for large enough n.…”
Section: Background -The Erdős-ko-rado Theorem and Rainbow Matchingsmentioning
confidence: 96%
“…In [20,21] a version of this result was proved for t-intersecting pairs of hypergraphs, for large enough n.…”
Section: Background -The Erdős-ko-rado Theorem and Rainbow Matchingsmentioning
confidence: 96%
“…If |F| = m and its u-cascade form is given by (11), then it follows from the Kruskal-Katona Theorem [4,3] that…”
Section: Preliminariesmentioning
confidence: 99%
“…A simple computation shows that m(α, β) = 1 if α + β > 1, and m(α, β) = 1 4 if α + β = 1. In [11] it is shown that if max{α, β} ≤ 1 2 then m(n, α, β) = αβ…”
Section: Introductionmentioning
confidence: 99%
“…, A k of a given family F. The paper [14] analyses this problem in general, particularly showing that, for k sufficiently large, both the sum and the product are maxima if A 1 = · · · = A k = L for some largest t-intersecting subfamily L of F. Therefore, this problem incorporates the t-intersection problem. Solutions have been obtained for various families (see [14]), including [n] r (see [5,7,25,29,39,43,46,48,49]), 2 [n] (see [14,38]), [n] r (see [15]), families of integer sequences [6,16,25,41,42,47,49,51], and families of vector spaces [44]. Most of these results tell us that, for the family F under consideration and for certain values of k, the sum or the product is maximum when A 1 = · · · = A k = L for some largest t-star L of F. In such a case, L is a largest t-intersecting subfamily of F. Remark 1.…”
Section: Introductionmentioning
confidence: 99%